1998
DOI: 10.1111/j.1744-7429.1998.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Reproductive Biology of Miconia calvescens DC (Melastomataceae), an Alien Invasive Tree on the Island of Tahiti (South Pacific Ocean)1

Abstract: Miconia calvescens DC (Melastomataceae) is a dominant invasive species in the tropical oceanic island of Tahiti (French Polynesia, South Pacific Ocean), where it was introduced as an ornamental plant. Whereas this small tree is sparse in its native range of Central America, it has spread in Tahiti into a wide variety of habitats including native wet forests. The remarkable success of this invasion is due in great part to prolific reproduction: a mature tree can bear up to 220 inflorescences with an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 29 publications
1
73
0
7
Order By: Relevance
“…Though the growth rate has been estimated heuristically, we do not expect that it differs from 0.3 significantly. This rate also conforms closely to the actual expansion of the tree on Tahiti, from a single tree in 1937 to dense monotypic stands covering 70,000 ha in the early 1990s, though theoretically the tree is capable of spreading at a much higher rate (Meyer, 1998a).…”
Section: Growth Functionsupporting
confidence: 75%
“…Though the growth rate has been estimated heuristically, we do not expect that it differs from 0.3 significantly. This rate also conforms closely to the actual expansion of the tree on Tahiti, from a single tree in 1937 to dense monotypic stands covering 70,000 ha in the early 1990s, though theoretically the tree is capable of spreading at a much higher rate (Meyer, 1998a).…”
Section: Growth Functionsupporting
confidence: 75%
“…(Mori & Pipoly 1984) e M. calvescens DC. (Meyer 1998). Porém, essas duas espécies apresentam fl oração mais sincrônica e limitada no tempo, referida na literatura como big bang, enquanto em M. angelana a fl oração apresenta múltiplos episódios ao longo de quase um mês, o que indicaria uma fl oração do tipo múltiplo bang (Gentry 1974).…”
Section: Discussionunclassified
“…We did not find any correlations between flowering and fruiting with precipitation levels in the study areas. In fact, in seasonal tropical forests, the main factor triggering the flowering and fruiting are differences in precipitation (Mori & Pipoly 1984, Meyer 1998, Aragão et al 2005, Santos et al 2010, but in areas with low seasonal climate photoperiod is indicated as the only mechanism that can be attributed to synchronous flowering (Borchert et al 2005). …”
Section: Discussionmentioning
confidence: 99%